CHILDFREE VERSUS GOD'S MANDATE: A CONTEXTUAL THEOLOGICAL PERSPECTIVE ON PROCREATION AND THE FAMILY - Martin Hasonangan Silaen; Riris Johanna Siagian (RADJA PUBLIKA, 2025)
This paper first examines the phenomenon of childfree as a modern lifestyle choice that challenges traditional theological views on God's mandate to multiply and fill the earth (Genesis 1:28). This phenomenon emerged as a reflection of changing values ​​in global society that increasingly emphasize individual autonomy, gender equality, and responsibility for social and ecological crises. In this context, childfree views are often considered contrary to God's will, while on the other hand, they can be understood as a form of ethical awareness of life, the environment, and human relationships. This study explores the theological meaning of procreation in the Christian faith not only as a biological act, but also as human participation in God's creative work, manifested through love, responsibility, and service within the family community. God's mandate to multiply is reinterpreted not merely as a literal command, but as a call to nurture life and build relationships that reflect God's love. The childfree lifestyle choice needs to be viewed through a dialogue between the biblical text and the modern human context, so that the church can present a relevant, inclusive, and liberating understanding. This research uses a descriptive qualitative method with a theological and contextual literature review to analyze the relationship between childfree, God's mandate, and family theology from a contextual perspective.